Nightingale - Fagan, Deva (Atheneum Books for Young Readers, 2022)
After twelve-year-old Lark, determined to escape her squalid life, steals a magical sword from the Royal Museum, she reluctantly becomes the next Nightingale, destined to vanquish an ancient evil.